2001
DOI: 10.1038/sj.ejhg.5200753
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis – a total genome-scan for susceptibility genes suggests a locus on chromosome 4q24-q27

Abstract: Allergic rhinitis is a common disease of complex inheritance and is characterised by mucosal inflammation caused by allergen exposure. The genetics of closely related phenotypes such as asthma, atopy and to some extend atopic dermatitis has attracted attention in recent years. Genetic reports of allergic rhinitis on the contrary have as yet been most sparse. To identify candidate regions holding genes for allergic rhinitis we performed a total genome-scan on affected sib-pair families. From 100 Danish sib-pair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 13 publications
2
57
2
Order By: Relevance
“…13 The linkage peak in the 2q32 region observed here for AR is about 40 cM apart from the linked region indicated in the Danish scan. 12 The other regions, 1p36 and 4q13, detected in the Japanese genome scan and 4q24-27 detected in the Danish screen were not replicated here. Lack of replication between the results of the French, Danish and the Japanese studies may be explained by either statistical issues (spurious detection of linkage, due to multiple tests, and/or lack of power) or by the heterogeneity between samples in terms of the phenotype definition (based only on questionnaire in the EGEA and Japanese studies and based on both questionnaire and clinical examination in the Danish study) and/or by the mode of ascertainment of the families.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…13 The linkage peak in the 2q32 region observed here for AR is about 40 cM apart from the linked region indicated in the Danish scan. 12 The other regions, 1p36 and 4q13, detected in the Japanese genome scan and 4q24-27 detected in the Danish screen were not replicated here. Lack of replication between the results of the French, Danish and the Japanese studies may be explained by either statistical issues (spurious detection of linkage, due to multiple tests, and/or lack of power) or by the heterogeneity between samples in terms of the phenotype definition (based only on questionnaire in the EGEA and Japanese studies and based on both questionnaire and clinical examination in the Danish study) and/or by the mode of ascertainment of the families.…”
Section: Discussionmentioning
confidence: 58%
“…However, accumulating indication for linkage across studies may be more important than unreplicated high linkage peaks to identify regions of interest. The present study is the third published genome scan of AR after one screen conducted in a Danish sample 12 and another one in a Japanese one. 13 The 9q22-q34 region detected for potential linkage to AR in our sample was also reported in the Japanese scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15 Our other three regions of linkage are new regions, as only the 4q24 region has been reported once to be linked to allergic rhinitis. 16 However, these regions contain several candidate genes potentially involved in asthma or asthma-related phenotypes. 5,15,17 Following these linkage findings, bivariate association analysis of SPTQ and FEV 1 /H 2 with markers in 5q31 showed significant association with two SNPs, rs2069885 and rs2069882, within IL9 gene in males.…”
Section: Sex-specific Qtl Underlying Asthma Phenotypes H Aschard Et Almentioning
confidence: 99%
“…We have previously reported linkage of allergic rhinitis to chromosome 4q24 -27 in a genome scan of Danish sib-pair families (LOD score 3.26). 10 In a recent fine-mapping study, we found evidence of linkage of additional atopy phenotypes to the same region, including increased serum levels of specific IgE (positive RAST test) and asthma. 11 The IL2 gene is located at 4q27 and consists of four exons.…”
Section: Introductionmentioning
confidence: 99%